Modelling, simulation and factorial design as tools for the in silico process optimisation of fructooligosaccharide production by immobilised fructosyltransferase in a basket reactor. (January 2014) - Soares, Mónica Beatriz Alvarado-Huallanco; Rodrigues, Maria Isabel; Maugeri-Filho, Francisco
Abstract: Modelling, simulation and optimisation of the production of fructooligosaccharides (FOS) by fructosyltransferase immobilised on inorganic niobium support and applied in a basket reactor (BR) were used for in silico optimisation of the process. Simulink and MATLAB 6.0 were used as computational tools. The kinetic process data were obtained experimentally using purified fructosyltransferase produced by Rhodotula sp. Optimisation experiments were carried out using simulation, according to the factorial design methodology, using a two central composite rotatable design. In the first design, the variables with the highest influence were determined; in the second design, the conditions to produce FOS were optimised. The optimum conditions were 14 Ui /ml for the activity of enzyme, immobilised in a niobium ore, and a stirring speed of 45 rpm. Under these conditions, FOS yield was 50.6% after 24 h of synthesis, at 50°C and pH 4.5. The results demonstrated the good efficiency of the BR, as well as showing that the film mass transfer coefficient around the biocatalyst has a significant influence during the reaction and production of FOS.